Big Events and Urban Governance in China: Experience from the Youth Olympic Games in Nanjing. Issue 1 (2nd January 2016) - Duan, Jin; Yi, Xin; Kunzmann, Klaus R.
Abstract: In 2009, on short notice, the City of Nanjing decided to bid for the Youth Olympics in 2014. This was done in order to demonstrate that the former capital city of China could compete with economically thriving city regions of the country, such as Shanghai, Beijing, Chongqing or Guangzhou. The event was driven by the local government in order to create opportunities for new urban development in a slowly stagnating property market and to seek Central Government support for accelerating the development of public infrastructure. In 2009, the decision went to Nanjing. With the support of the Central Government, Nanjing could attract the event to the city. The paper will explore whether the expectations of the local government came true. It will describe how the city prepared for the event and what challenges the city had to face to arrange the grounds for the event. It will also assess the positive and negative implications of using such an event for urban development. Some general conclusions will be drawn at the end, i.e. whether eventdriven urban development in China is unavoidable as a means of profiling cites in times of globalization; and to what extent such events have an impact on city governance in Chinese cities.